Assessing Awareness, Attitudes, and Practices of Undergraduate Management Students Toward Green and Sustainable Public Health Initiatives - Khatiwada, Bipana; Rana, Roshani (International Journal of Atharva, 2026)
Background: The inclusion of environmental sustainability in public health, known as Green and Sustainable Public Health Initiatives (GSPHI), is very important for dealing with modern-day challenges in the global scenario. As future leaders in organizations, the readiness of undergraduate management students to support GSPHI is very important, but their AAPs are not well studied, especially in a Nepal scenario. Objectives: This study was designed to evaluate the AAPs of undergraduate management students towards GSPHI, explore the relationships between awareness, attitudes, and practices, investigate their effects on future intentions, and determine the contributing demographic factors. Methods: A quantitative, cross-sectional study was carried out among 202 undergraduate management students from a Pokhara University-affiliated college in Kathmandu, selected through convenience sampling. The data were collected through a structured, 25-item questionnaire covering five domains: Awareness, Personal Engagement, Perception of Corporate Social Responsibility (CSR), Attitudes Towards Policy and Governance, and Future Intentions and Advocacy. Findings: Students demonstrated moderately high awareness (mean scores: 3.50–4.13) and strongly positive attitudes towards policy (means: 4.00–4.18) and CSR (means: 3.96–4.15). Personal engagement was moderate (means: 3.57–3.73). Future intentions were high (means: 3.86–4.15). Regression analysis revealed that Attitudes Towards Policy and Governance (β=0.436, p<0.001) and Perception of CSR (β=0.247, p=0.004) were significant positive predictors of Future Intentions and Advocacy, explaining 53.9% of its variance. Awareness and Personal Engagement did not show significant unique predictive effects in the multivariate model. Conclusion: Though students of management have a positive attitude and awareness regarding GSPHI, a gap exists between them and the actual expression of such attitude and awareness as personal practices and intentions to advocate for it. Educational initiatives must fill this gap to ensure effective integration, participation, and strategic emphasis on the role of CSR and policy advocacy for students of management. Novelty: This study is the first to conduct a holistic evaluation of AAPs regarding GSPHI among students of management in Nepal, with a unique five-domain model linking personal practices, CSR, policy, and professional intentions.